2015
DOI: 10.3358/shokueishi.56.118
|View full text |Cite
|
Sign up to set email alerts
|

ウシ由来大腸菌が保有する病原性に関与する遺伝子群の包括的実態調査

Abstract: Pathogenic genes such as stx1, stx2, STh gene, STp gene, LT gene, invE, eae, aggR, afaD, astA, cdt and cnf were investigated in Escherichia coli isolated from cattle during Nov. 2012 and Aug. 2013. Plural pathogenic genes were concurrently detected by multiplex PCR, and screen-positive genes were confirmed and sub-classified by PCR. Among 100 cattle investigated, 180 E. coli strains with diarrheic genes (DEC) were detected in 79 cattle, and 45 of them, isolated from 32 cattle, were Shiga toxin-producing E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
(8 reference statements)
3
7
1
Order By: Relevance
“…Although EAEC is relatively rare among humans, this pathotype is still significantly more prevalent in human fecal samples compared to those of animals. Our results are consistent with the findings of Akiyama et al (31), who reported that aggR was not detected in any of the cattle-derived DEC examined. The reservoir for EAEC is likely humans.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Although EAEC is relatively rare among humans, this pathotype is still significantly more prevalent in human fecal samples compared to those of animals. Our results are consistent with the findings of Akiyama et al (31), who reported that aggR was not detected in any of the cattle-derived DEC examined. The reservoir for EAEC is likely humans.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, foods and fecal specimens were screened using a multiplex realtime PCR protocol. Our experiments revealed that enterovirulence genes, especially astA and eae, were more common in cattle, pigs, and chickens than has been previously reported in studies using culture methods (31). Domestic animals are thought to be natural carriers of EAST1EC and EPEC.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Bacterial strains and template DNA preparation: E. coli strains carrying virulence genes were isolated from the intestinal ingredients of cattle, as previously described (13). Forty-five STEC strains isolated from 32 Japanese Black cattle (20 oxen and 12 cows) bred in Hyogo Prefecture were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…None of the faecal samples contained the four markers simultaneously, indicating that cattle in France were not likely to be a reservoir of O104:H4, but results of the test for aggR were not reported (Auvray et al, 2012). In a recent study of 100 clinical cases in cattle in Japan, no EAEC isolates, as assessed by the presence of aggR, were detected (Akiyama et al, 2015).…”
Section: Public Health Significance Of Eaec Related To the Handling mentioning
confidence: 97%